ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA SMA PADA MATERI LIMIT FUNGSI - Yusdiana, Bentang Indria; Hidayat, Wahyu (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This research is a qualitative descriptive research that aims to analyze the level of students' reasoning ability in solving the problem on material function limit by categorizing high, medium, and low mathematical reasoning ability. The subjects of the study were 20 students of class XII. A form of data retrieval is the provision of 4 items about written tests and interviews on selected subjects. Based on the results of the analysis, the average value of the whole matter of the instrument of mathematical reasoning ability derives 89% for the indicator performing calculations based on the applicable mathematical formula or rules, 84% and 64% of the indicators draw conclusions and 93% for the indicator to make the estimate so that if totaled and averaged 83%. Then the mathematical reasoning ability of high school students of class XII is appertaininghigh.